(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to investigate the influence of physical activity on people with obesity through an integrative review. Methodology: This research on the influence of physical activity on obesity was carried out through an integrative review in the SciELO, DOAJ and RBONE databases, using the term “obesity AND physical activity”. Results: It was possible to verify that the main causes of obesity incidence are related to sedentary habits that humanity has been acquiring. Possibly influenced by the abuse of technological means of communication, combined with other disorders of a biopsychosocial character characteristic of the society in which we live. In this sense, predisposed to affect all audiences, regardless of their age and/or socioeconomic conditions. Conclusion: It is evident that a good physical activity program, when fitted into daily life, can make all the difference in this scenario. Thus, making an exceptional contribution to the prevention and control of obesity. Furthermore, it was found that physical activity is an essential factor in the prevention and treatment of obesity. It is suggested to raise awareness of all audiences to practice physical activity and, consequently, reduce the number of obese people.